2022
DOI: 10.3389/fpsyt.2021.804637
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Professionals' Perception of Stress During COVID-19 Pandemic in Iran: A Qualitative Study

Abstract: BackgroundThe health care professionals have a unique role in controlling the pandemic of COVID-19 and decreasing its mortality and morbidity. The burden of care and psychological impact of working in this circumstance can be unfavorable for many caregivers. In this qualitative study, the health care professionals' perception of stress during COVID-19 pandemic in Iran was assessed and several implications were proposed.Materials and MethodsThe participants were selected among staff who were providing medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The detection and treatment of PTSD in people after a disaster has become a major concern in medical psychology ( 4 ). During the SARS epidemic, medical staff were more susceptible to stress disorders than executives due to the need to cope with the potential risk of infection to themselves and their families ( 5 ) and the threat of a shortage of personal protective equipment ( 6 ), and some medical staff were afraid to go home after work or even considered quitting ( 7 ). COVID-19 has been spreading worldwide over the past 2 years, and the global impact is now growing rapidly with the discovery of the SARS-CoV-2 Omicron variant (B.1.1.529) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The detection and treatment of PTSD in people after a disaster has become a major concern in medical psychology ( 4 ). During the SARS epidemic, medical staff were more susceptible to stress disorders than executives due to the need to cope with the potential risk of infection to themselves and their families ( 5 ) and the threat of a shortage of personal protective equipment ( 6 ), and some medical staff were afraid to go home after work or even considered quitting ( 7 ). COVID-19 has been spreading worldwide over the past 2 years, and the global impact is now growing rapidly with the discovery of the SARS-CoV-2 Omicron variant (B.1.1.529) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that an especially serious COVID-19 experience, work stress and barriers in health care provision affected the QoL of hospital HCWs. Regarding personal COVID-19 experience, a mechanism may be that our HCWs felt lonely, angry, guilty and worried about their own health and about the high possibility of spreading the infection, even to their relatives [ 24 , 28 , 29 , 35 , 41 43 ]. In a study by Nohesara et al, HCWs expressed feelings of guilt for being possible carriers, due to lack of treatment facilities and vaccinations, and for not having the chance to take care of the loved one [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, they might perceive essential work stress because of the origin of their work, such as long hours and night shifts, a heavy workload (responsibilities, patients, pressure loads), dealing with pain and emotional distress, and facing a shortage of HCWs [ 14 , 36 , 37 ]. Second, they may have experienced additional PanMan stress due to new pandemic occupational changes, such as redeployment (loss of team and routine), no possibility of taking proper breaks or time off, a lack of preparedness, non-efficient management, poor working conditions (safety concerns, lack of and use of PPE, disinformation, ambiguity of performance), lack of effective treatments specifically for COVID-19, and death of their patients [ 10 , 13 , 25 , 30 32 , 40 , 41 , 43 ]. Evidently, experiencing these various stressful work and PanMan circumstances may have accumulated and thus could have had an impact on all domains of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that the COVID-19 pandemic has generated substantial increases in the incidence of depression, anxiety, and acute stress disorders (5)(6)(7). There is widespread consensus that mental health problems are increasing and are mainly caused by the COVID-19 pandemic, particularly due to social isolation, fear of infection, parental distress, and family financial stress (8,9).…”
Section: Introductionmentioning
confidence: 99%